Analisis Niat Menyalurkan Infaq dengan Menggunakan QRIS pada Generasi Z dengan Model UTAUT: Peran Altruisme dan Religiusitas - Dewita Puspawati; Novel Idris Abas; Kurnia Rina Ariani; Ihsan Cahyo Utomo; Lintang Kurniawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine the effect of the UTAUT model on the intention to use QRIS in distributing infaq with the addition of altruism and religiosity variables. The sample of this study was Generation Z in Central Java. The number of samples used in this study was 345 respondents. The data analysis technique used SEM PLS. The results showed that performance expectancy, social influence, facilitating conditions, and altruism influenced the intention to use QRIS in distributing infaq. However, effort expectancy and religiosity did not influence. The implication of this study is that infaq management institutions and mosques need to create QR Codes to facilitate the community in donating infaq.